2011
DOI: 10.1007/s13312-011-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for prolonged shedding of 2009 H1N1 influenza virus

Abstract: This retrospective study was conducted to estimate the shedding of 2009 H1N1 virus and the risk analysis by review of medical charts, laboratory and radiological findings of all inpatients with confirmed pandemic influenza A (H1N1) at a provincial pediatric hospital. A total of 41 cases attending the inpatient department between 15 November, 2009 to 14 December, 2009 were included. Prolonged and discontinuous shedding of 2009 H1N1 virus (median, 10 days; range, 2 to 24 days) were detected by real-time RT-PCR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…However, data on factors associated with prolonged shedding of respiratory viruses is limited with the exception of influenza virus in mainly immunocompetent populations and coronavirus in HCT recipients. 9, 26, 27 The present study showed initial high viral load was a risk factor for prolonged HRV shedding in HCT recipients, consistent with our previous study of coronavirus. 9…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, data on factors associated with prolonged shedding of respiratory viruses is limited with the exception of influenza virus in mainly immunocompetent populations and coronavirus in HCT recipients. 9, 26, 27 The present study showed initial high viral load was a risk factor for prolonged HRV shedding in HCT recipients, consistent with our previous study of coronavirus. 9…”
Section: Discussionsupporting
confidence: 92%
“…Viral shedding duration is often used as an endpoint in clinical trials of new antivirals [23] , [24] , [25] , and identifying risk factors for prolonged shedding is thus critical for appropriate stratification of patients in randomized trials. However, data on factors associated with prolonged shedding of respiratory viruses are limited, with the exception of influenza virus in mainly immunocompetent populations and coronavirus in HCT recipients [9] , [26] , [27] . The present study showed initial high viral load was a risk factor for prolonged HRV shedding in HCT recipients, consistent with our previous study of coronavirus [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Seven cases received oseltamivir 48 h after admission or later, including 4 children who died. The repeated tests for influenza A (H1N1) virus from nasal pharyngeal swabs in forty-one cases revealed that the mean days of viral shedding were 11.4 d with a range of 2 d to 21 d [3], and the shedding was longer than the findings reported by Li IW [4][5][6]. For 6 ICU cases, the authors had the chance to monitor the viral shedding after the first one or two times of negative result; 4 of them transiently turned positive for 1 to 2 d, all of these four cases developed severe complications and 3 of them had co-infections; the influenza A (H1N1) RT-PCR transiently turned positive after it had become negative in these patients, suggesting the virus shedding was discontinuous [3].…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for this remain to be elucidated. Immunosuppression, drug‐resistant influenza strains, pediatric age, and delayed treatment initiation have previously been associated with PVS . Most recent publications on influenza infections in SOT recipients report hospitalization rates of 63–100% .…”
Section: Discussionmentioning
confidence: 99%